Analisis Kreativitas Guru Matematika Dalam Mendesain Pembelajaran Di Masa Pandemi Covid-19 - Rosana, Rosana; Andriani, Parhaini; Hesikumalasari, Hesikumalsari (Jurnal of Math Tadris, 2022)
The purpose of this study was to describe the creativity of mathematics teachers in designing learning during the covid-19 pandemic. This research is a qualitative research with the type of case study research that analyzes the creativity of mathematics teachers in designing learning during the covid-19 pandemic. The subjects in this study were mathematics teachers in grades VII, VIII and IX at SMPN 5 Sekotong. The instruments used in this study were interview guidelines and documentation. Data analysis used is data reduction, data presentation, and drawing conclusions. The results of this study are that the creativity of mathematics teachers in designing learning can be seen from the activities of each teacher during the process of designing the lesson. Where there are certain things that at the time of designing (designing) learning during this pandemic, the teacher made slight modifications, namely in determining competency achievement indicators (GPA) that did not burden students, the teacher emphasized more on student character building, including building student motivation to studying in school. The time allocation is also shortened because students who enter the school are divided into several sessions, so that students can keep their distance while studying in class and not cause crowds in the school environment. The teacher chooses to use the discussion and question and answer method where the discussion and question and answer method is carried out online using the WA Group. This is a solution for students to stay active in learning and comply with Health protocols.